The moving minimum audible angle is smaller during self motion than during source motion - Brimijoin, W. Owen; Akeroyd, Michael A. (Frontiers in Neuroscience, 2014)
We are rarely perfectly still: our heads rotate in three axes and move in three dimensions, constantly varying the spectral and binaural cues at the ear drums. In spite of this motion, static sound sources in the world are typically perceived as stable objects. This argues that the auditory system – in a manner not unlike the vestibulo-ocular reflex – works to compensate for self motion and stabilize our sensory representation of the world. We tested a prediction arising from this postulate: that self motion should be processed more accurately than source motion. We used an infrared motion tracking system to measure head angle, and real-time interpolation of head related impulse responses to create “head-stabilized” signals that appeared to remain fixed in space as the head turned. After being presented with pairs of simultaneous signals consisting of a man and a woman speaking a snippet of speech, normal and hearing impaired listeners were asked to report whether the female voice was to the left or the right of the male voice. In this way we measured the moving minimum audible angle (MMAA). This measurement was made while listeners were asked to turn their heads back and forth between ± 15° and the signals were stabilized in space. After this “self-motion” condition we measured MMAA in a second “source-motion” condition when listeners remained still and the virtual locations of the signals were moved using the trajectories from the first condition. For both normal and hearing impaired listeners, we found that the MMAA for signals moving relative to the head was ~1-2° smaller when the movement was the result of self motion than when it was the result of source motion, even though the motion with respect to the head was identical. These results as well as the results of past experiments suggest that spatial processing involves an ongoing and highly accurate comparison of spatial acoustic cues with self-motion cues.